Hubungan Relative Fat Mass dengan Volume Kelenjar Prostat pada Pasien Benign Prostatic Hyperplasia - Alexandro Manurung; Eka Yudha Rahman; Oski Illiandri (Homeostasis, 2020)
Abstract: More than 70 million cases of degenerative diseases in men are benign prostatic hyperplasia (BPH). Relative fat mass (RFM) is a method of measuring body fat that more accurate than body mass index (BMI). Increased fat mass in BPH patients have risk to increase  prostate proliferation more quickly. The aimed of this study was to determine the associations of Relative Fat Mass with prostate gland volume in Benign Prostatic Hyperplasia patients. This research used analytic observational method with cross-sectional approach. Samples were taken by purposive sampling technique with the number samples of this study were 34 samples. Data analysis using linear regression test. The results of average prostate volume was 33.45 ± 5.55 cc and the average RFM value was 28.16 ± 3.93. There is a significant associations (r = 0.381; p = 0.026) with a weak degree of correlation. between RFM and prostate volume in BPH patients.  Keywords: BPH, RFM, prostatic volume  Abstrak: Lebih dari 70 juta kasus penyakit degeneratif pada laki-laki adalah benign prostatic hyperplasia (BPH).Relative fat mass (RFM) merupakan metode pengukurannya lemak tubuh yang memiliki hasil lebih akurat dibandingkan body mass index (BMI). Peningkatan massa lemak pada pasien BPH dapat mengalami risiko meningkatkan proliferasi prostat lebih cepat. Tujuan penelitian ini untuk mengetahui hubungan Relative Fat Mass dengan volume kelenjar prostat pada pasien Benign Prostatic Hyperplasia. Penelitian ini menggunakan metode penelitian observasional analitik dengan pendekatan cross-sectional. Sampel diambil dengan teknik purposive sampling dengan jumlah sampel penelitian ini didapatkan 34 sampel. Analisis data menggunakan uji regresi linear.. Terdapat hubungan yang bermakna (r=0.381; p=0.026) dengan derajat korelasi lemah Kata-kata kunci: BPH, RFM, volume prostat